Islam dan Liberalisme: Analisis Tafsir Maudhu’i - Fursan Ruhbani; Ia Aulia; Imam Musyaffa Mujahadah; Ina Nurseha; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this research is to study more broadly related to Islam and Liberalism. This study used a qualitative method with data collection using the maudhu'i interpretation method. The formal object of research is about the science of interpretation. The material object is the interpretation of Q.S. Al-Baqarah verse 256, Q.S. Al-Isra verse 31, and Q.S. Ar-Rad verse 11. The results of the discussion of this study are that the verses studied using the maudhu'i interpretation method have a clear basis for explaining to the people and can be practiced. This research concludes that Q.S. Al-Baqarah verse 256, Q.S. Al-Isra verse 31, and Q.S. Ar-Rad verse 11 is relevant to be used as the foundation of Islam and liberalism.